Exploring Interventional Radiology: A Multicentre Study on Saudi Medical and Radiology Technology Students’ Perspectives - Aldahery S; Qwader R; Asiri RT; Al-Alfy A; Bushara L; Qurashi A; Alhazmi FH; Gareeballah A; Alahmadi AAS; Yousef M; Osman H; Alsharif W; et al. (Advances in Medical Education and Practice)
Shrooq Aldahery,1 Renad Qwader,1 Raghad Talal Asiri,1 Afnan Al-Alfy,1 Lubna Bushara,1 Abdulaziz Qurashi,2 Fahad H Alhazmi,2 Awadia Gareeballah,2 Adnan AS Alahmadi,3 Mohamed Yousef,4 Hanady Osman,4 Walaa Alsharif,2 Khalid M Alshamrani5– 7 1Department of Applied Radiologic Technology, College of Applied Medical Sciences, University of Jeddah, Jeddah, Saudi Arabia; 2Diagnostic Radiology Technology Department, College of Applied Medical Sciences, Taibah University, Madinah, Saudi Arabia; 3Radiologic Sciences Department, Faculty of Applied Medical Sciences, King Abdul Aziz University, Jeddah, Saudi Arabia; 4Radiological Sciences Program, Batterjee Medical College, Jeddah, 21442, Saudi Arabia; 5College of Applied Medical Sciences, King Saud bin Abdulaziz University for Health Sciences, Jeddah, Saudi Arabia; 6King Abdullah International Medical Research Center, Jeddah, Saudi Arabia; 7Ministry of the National Guard - Health Affairs, Jeddah, Saudi ArabiaCorrespondence: Shrooq Aldahery, Email Staldahery@uj.edu.saBackground: Interventional radiology (IR) is a subspecialty of diagnostic radiology that uses image-guided radiological methods to carry out minimally invasive procedures. Medical schools in Saudi Arabia minimally expose students to IR unless it is part of an elective rotation. The study aims to gauge how well informed medical and radiology technology students are regarding the variations in educational and clinical experiences offered at different universities in Jeddah, Saudi Arabia. It also aims to assess students’ interest in IR as a potential career path and their opinions about their life experiences concerning the department’s future.Methods: This study used a cross-sectional study design. Between April and May 2023 in Jeddah, Saudi Arabia, students studying radiology technology and medicine who were in their second year to internship year were given access to a cross-sectional questionnaire.Results: The study found that 31.5% of the students reported having poor knowledge of IR, while 7.8% reported not knowing about it at all. Additionally, 45.9% of respondents felt that their knowledge was adequate, while a minority of 14.7% reported having an excellent understanding of IR concepts. Therefore, in order to enhance students’ knowledge about IR, IR courses should be introduced early into curricula, IR symposiums and conferences.Conclusion: The limited exposure of medical and radiology technology students to IR was highlighted. Over one-third indicated interest in IR as a career, with radiology technology students demonstrating greater familiarity. Enhancing IR education through early curriculum integration, symposiums, and conferences is essential. Furthermore, addressing the lack of a standardized radiology curriculum in Saudi medical schools could further enhance IR awareness and career development.Keywords: interventional radiology, awareness, students, knowledge, career